LECTURERS’ POLITENESS STRATEGIES IN EFL CLASSROOM WITH MULTICULTURAL BACKGROUND - Dwi Fita Heriyawati; Stifania Yuliana Siba; Teguh Sulistyo (LITERA, 2019)
The choice of words used by the lecturer such as politeness strategies in the classroom interaction is very important, not only for controlling the classroom but also for the process of acquiring the language itself. This study aimed to investigate lecturer’s politeness strategies in criticizing teaching performance of students with multicultural backgrounds in a microteaching class. This qualitative study was conducted with the students from multicultural backgrounds. The subject of this study was a lecturer who taught Microteaching. The findings of this study showed that there were four most frequent criticism strategies used by the lecturer: demand for change, indicating standard, advice about change and other hint. In addition, the highest proportion of politeness strategies applied by the lecturer was occupied by positive politeness, off-record strategy, bald on record, and negative politeness. It implied that the lecturer mostly applied positive politeness in criticizing the students, in order to save the students’ face, get closer and give more positive feedback to help students develop their teaching performance. The facts also proved that students’ multicultural background did not affect too much lecturer’s decision in applying politeness strategies, yet it needed to be very careful in delivering them. Keywords: politeness strategies, criticism, multicultural backgrounds